2018
DOI: 10.3389/fsoc.2018.00030
|View full text |Cite
|
Sign up to set email alerts
|

Materialities in and of Institutional Care for Elderly People

Abstract: Since some decades, nursing homes for elderly people are discussed as "total institutions" in the sense of Erving Goffman. However, this line of research has not clarified yet as to how the creation of a totalizing nursing home is actually achieved on the basis of everyday practices and interactions. In my contribution I address this research gap by looking at how material and spatial arrangements in nursing homes for elderly people affect the ways its residents are socially constructed. By drawing on Goffman'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…As concluded by Calkins (2009), the term ‘non-institutional’ is frequently used to denote quality in the design of nursing home settings, based on an implicit assumption that there is an agreement on what the antithesis of institutional means. The general ambition to avoid institutional features in nursing home design is (implicit or explicit) derived from Goffman's (19903) definition of the ‘total institution’ (Artner, 2018). According to Goffman, residents in a total institution have little control over their lives and their personal identity is threatened.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As concluded by Calkins (2009), the term ‘non-institutional’ is frequently used to denote quality in the design of nursing home settings, based on an implicit assumption that there is an agreement on what the antithesis of institutional means. The general ambition to avoid institutional features in nursing home design is (implicit or explicit) derived from Goffman's (19903) definition of the ‘total institution’ (Artner, 2018). According to Goffman, residents in a total institution have little control over their lives and their personal identity is threatened.…”
Section: Introductionmentioning
confidence: 99%
“…Goffman also concluded that the total institution is manifested through environmental features such as locked doors and enclosed buildings. As discussed by, for example, Artner (2018), there is a lack of research on how the total institution is shaped through the everyday interactions involving material and spatial arrangement and the social actors in nursing home contexts. Reflecting this lack of research, the manifestations of an ambition for a non-institutional design in nursing homes tend to be based on general associations of institutions as, for example, long corridors and visible nursing stations, rather than more in-depth understandings of how characteristics of a total institution are manifested.…”
Section: Introductionmentioning
confidence: 99%
“…Despite sharing these characteristics, life within such homes is extremely diverse. Existing literature on old-age inpatient care refers to organizational differences to explain this empirically observable heterogeneity (Artner, 2018; Barnes, 2006; Döbler, 2019b; Federal Statistical Office, 2016; Kane, 2001; McDaniel & Stumpf, 1993). This presumption is common but not limited to research drawing on Goffman’s (1961) work on inpatient housing and care elaborated in “asylums” (Heinzelmann, 2004; Kelle et al, 2014).…”
Section: Study Backgroundmentioning
confidence: 99%
“…Furthermore, culture is “insubstantially” interpreted as the cause and effect of different but regularly appearing ways of living, thinking, and (inter-)acting (Hall & Neitz, 1993; Jenks, 1993). These are supposed to offer particular solutions to ontological, epistemological, and teleological problems common to all humans and issues central to life (Artner, 2018; Hills, 2002; Tam, 2014; Vries, 2018) and to reveal themselves in people’s doings and sayings (Lehmann & Brinkmann, 2019). This conceptualization makes culture a system of signs and symbols as well as a mode or medium of comparisons (Jenks, 1993).…”
mentioning
confidence: 99%
“…One example is an investigation into how things are sorted out when someone moves into a care institution (Depner, 2015). Research has also revealed how objects co-produce care in care institutions (Artner and Atzl, 2016;Depner, 2017;Artner, 2018). The importance of objects when caring for and supporting people with dementia has also been shown (e.g., Buse and Twigg, 2014;Depner and Kollewe, 2017).…”
Section: Studying Materials Things In Old Age From a Social And Cultural Science Perspectivementioning
confidence: 99%